2010
DOI: 10.1016/j.jhazmat.2010.08.102
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and kinetic analysis of phosphorus adsorption from aqueous solution using waste alum sludge

Abstract: Excess phosphorus (P) in wastewaters promotes eutrophication in receiving waterways. A cost-effective method such as use of novel low-cost adsorbents for its adsorptive removal would significantly reduce such impacts. Using batch experiments, the intrinsic dynamics of P adsorption by waste alum sludge (an inevitable by-product of drinking water treatment plants)was examined. Different models of adsorption were used to describe equilibrium and kinetic data, calculate rate constants and determine the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 27 publications
3
56
1
1
Order By: Relevance
“…Therefore, the sorption of phosphorus from aqueous solution onto the marble dust sorbent was found to follow the pseudo second order kinetic equation. Similar conclusion was also reported for the sorption of phosphorus onto various sorbent surfaces [5,8]. Furthermore, the pseudo second order is based on the assumption that sorption follows a second order mechanism, with chemisorption as the rate limiting step.…”
Section: Kinetic Modeling Of Phosphorus Sorptionsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, the sorption of phosphorus from aqueous solution onto the marble dust sorbent was found to follow the pseudo second order kinetic equation. Similar conclusion was also reported for the sorption of phosphorus onto various sorbent surfaces [5,8]. Furthermore, the pseudo second order is based on the assumption that sorption follows a second order mechanism, with chemisorption as the rate limiting step.…”
Section: Kinetic Modeling Of Phosphorus Sorptionsupporting
confidence: 79%
“…The sorbet amount of phosphorus was calculated from the concentrations in solution before and after sorption. Also the amount of phosphorus sorbet by natural material from the solution at equilibrium q e (mg/g) was computed using Equation (1) [5]:…”
Section: Batch Experimentsmentioning
confidence: 99%
“…Increasing interest in the usage of WWS for the removal of phosphate at the WWTP is seen in the past two decades in the form of many laboratory studies (e.g. Babatunde and Zhao 2010;Ippolito et al 2003;Yang et al 2009;Zhao et al 2007); however, the reuse of WWS at WWTP is rarely seen in practice. The reported studies on phosphate removals with WWS show that the sorption of phosphate is a two-stage process: a quick sorption followed by slow sorption (cited in Ippolito et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have discussed the kinetics of P adsorption from aqueous solution (Babatunde and Zhao, 2010;Sakadevan and Bavor, 1998), while few studies about adsorption kinetics of sediment P were reported. This paper attempted to carry on an initial study to adsorption kinetics of sediment P in all fractions.…”
Section: Static Adsorption Testsmentioning
confidence: 99%